A National Conservation Policy for a New Millennium—Building Opportunity, Extending Capacity and Securing Integration in Cultural Materials Conservation. Issue 2 (December 2015) - Sloggett, Robyn
Abstract : In Launceston, in October 1995, the Federal Government launched Australia's National Conservation Policy for the Conservation of Movable Cultural Heritage. This policy, developed for the Cultural Ministers Council (Australia), was one of the very few national materials conservation policies in the world. The associated strategy led to the development of important frameworks and tools for significance assessment, conservation planning, training, disaster preparedness and environmental guidelines, and in identification of skills gaps and research needs. The political, economic and technological environment in which conservators operate has changed considerably since 1995, and, with the majority of conservators engaged by public institutions, many constituencies in Australia remain relatively untouched by the work of the profession. As a result there exist many new opportunities for conservators to engage with individuals and communities, but a national focus is required to most effectively garner resources, avoid duplication and take advantage of new technologies. This paper examines the case for a new iteration of a national policy for the conservation of Australia's cultural heritage material, and outlines the work needed to achieve this.